Preparation and Crystal Structure of a New Uranyl Sulfate Templated by a Bis‐isothiouronium Cation. Issue 11 (22nd June 2020) - Charkin, Dmitri O.; Bezzubov, Stanislav I.; Siidra, Oleg I.; Borisov, Artem S.; Kalmykov, Stepan N.
Abstract : Crystals of a new uranyl sulfate (C2 N4 H8 S2 )[UO2 (SO4 )2 ]· 0.3H2 O (1 ) templated by a relatively rare bis‐isothiouronium cation, were formed upon evaporation of aqueous solutions containing uranyl acetate, thiourea, and excess sulfuric acid. The new compound is orthorhombic, P 21 21 21, a = 6.928(2) Å, b = 13.398(3) Å, c = 15.225(3) Å, Z = 2. Its crystal structure is comprised of [UO2 (SO4 )2 ] moieties linked by hydrogen bonds formed between the template cations and terminal oxygen atoms of the sulfate tetrahedra. The C2 N4 H8 S2 2+ template is most likely formed in situ during a redox reaction between uranyl cation and thiourea in a strongly acidic medium, with UO2 2+ partially reduced to U 4+ . Abstract :